STUDI PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN PT AIRASIA INDONESIA TBK DENGAN PT GARUDA INDONESIA (PERSERO), TBK MENGGUNAKAN RASIO LIKUIDITAS SAAT DAN SESUDAH PANDEMI (TAHUN 2019 SAMPAI TAHUN 2023) - Fitria Wati; Delia Putri Kirani; Risna Haryati; Itto Turyandi (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2024)
The aviation industry is one of the transportation sectors that has an important role in supporting community mobility and the economy of a country. PT Garuda Indonesia Tbk and PT AirAsia Indonesia are two airline companies in Indonesia that offer a variety of flight services with different market segmentations. The Indonesian aviation industry has experienced a negative impact due to Covid-19, where at the national level the flow of passengers from cargo has decreased quite fantastically from March 2020 to April 2020. Not only at the national level these two airlines also experienced a decrease in the number of passengers during the pandemic in 2020 and 2021, causing these two airlines to experience a significant decrease in revenue and profit in that period which had an impact on the ability of these two airlines to meet financial obligations and maintain their financial performance. This study attempts to assess the financial performance of PT Garuda Indonesia Tbk and PT AirAsia Indonesia by using Liquidity Ratio analysis which includes Current Ratio, Quick Ratio, Cash Ratio, Cash Turnover Ratio and Inventory to Net Working Capital, with data taken from financial statements for the 2019-2023 period. Both airlines experienced a significant decline based on five main financial ratios. The liquidity ratios of both companies are low which indicates difficulty in meeting short-term obligations.